Utilizing a Two-stage Design to Investigate the Safety and Potential Efficacy of Monthly Naltrexone Plus Once-daily Bupropion as a Treatment for Methamphetamine Use Disorder. Issue 4 (July 2016) - Mooney, Larissa J.; Hillhouse, Maureen P.; Thomas, Christie; Ang, Alfonso; Sharma, Gaurav; Terry, Garth; Chang, Linda; Walker, Robrina; Trivedi, Madhukar; Croteau, David; Sparenborg, Steven; Ling, Walter
Abstract : Objectives: This 2-stage open-label pilot study evaluated the safety and potential efficacy of naltrexone + bupropion as a pharmacotherapy for methamphetamine (MA) use disorder. Methods: The study was conducted in 2 stages of recruitment across 3 sites; 20 participants were enrolled in stage 1 and 29 participants were enrolled in stage 2. Eight weeks of open-label pharmacotherapy with a combination of extended-release injectable naltrexone (XR-NTX; Vivitrol) plus extended-release oral bupropion (BRP; Wellbutrin XL) were provided with a smartphone-assisted medication adherence platform. Participants met Diagnostic and Statistical Manual of Mental Disorders, 5th Edition criteria for severe MA use disorder, self-reported ≥20 days of MA use in the 30 days prior to consent, and submitted 3 MA-positive urine drug screens (UDS) out of 4 collected during screening. Participants attended clinic twice weekly for observed BRP dosing, UDS testing, assessments, and medical management; XR-NTX was administered at weeks 1 and 5. A BRP taper and follow-up visit occurred in week 9. Results: Analyses evaluated effects of XR-NTX + BRP to determine the number of "responders" according to a statistically predefined response criterion (6 of 8 MA-negative UDS during the last 4 weeks of medication). The 2-stage design required that stage 1 yield ≥3 responders to continue to stage 2; 11 of the 49 participants met responder criteria across both stages (5 in stage 1, 6 in stage 2). Conclusions: Under the statistical analysis plan, study "success" required ≥9 responders. With 11 responders, the study demonstrated sufficient potential of naltrexone plus bupropion as a combination pharmacotherapy for MA use disorder to warrant further study.